Membangun Kolaborasi Pustakawan dan Fakultas dalam Meningkatkan Keterampilan Literasi Informasi Mahasiswa - Attala Arsya Rania; Retno Sayekti (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2022)
The fast-moving, unlimited flow of information and the appearance of various publications of information sources both printed and non-printed make students as information users trapped in the many sources of information circulating and do not allow them to evaluate one by one. Therefore, it takes the role of librarians and academics to form an information literacy programme as an effort to improve students' information literacy skills. The purpose of this study is to find out and describe the extent to which the readiness of librarians and lecturers of UIN North Sumatra in building collaboration to form an information literacy learning curriculum programme in lectures. This research uses a descriptive qualitative approach with data analysis techniques using the Miles and Huberman model. The results stated that librarians and lecturers strongly support the implementation of collaboration to integrate information literacy into the learning curriculum. However, in reality, librarians and faculty are still not ready to assign librarians as teaching staff who will teach information literacy learning in the classroom. So the reviewer suggests that UIN North Sumatera library can move more actively to encourage librarians to various skill development activities that can improve teaching competence.